Acceptance and Commitment Therapy Intervention to Improve Psychological Symptoms in Diabetes Mellitus Patients - Limanauw, Marchellino Edmond Aprico; Keliat, Budi Anna; Putri, Yossie Susanti Eka; Rachmawati, Imami Nur (GLOBAL HEALTH SCIENCE GROUP, 2024)
Psychological problems that occur in DM patients need to be a serious concern. Psychological problems that occur in DM casein can be caused by health changes that occur due to natural DM disease. The purpose of this systematic search is to determine the benefits and implementation of acceptance and commitment therapy (ACT) in improving psychological symptoms in diabetes mellitus patients. Article search using systematic review method conducted on several electronic databases such as EBSCOhost, ProQuest, PubMed, ScienceDirect, Scopus, and International Archives of Health Science. The selected article is a study that uses an intervention design with a sample of diabetes mellitus patients, measures at least 1 psychological symptom, and is published in the last 10 years. Search results showed that 12 articles met the criteria for analysis. The psychological symptoms most often measured in these articles are depression, anxiety, and distress. The results showed that ACT was effective in improving psychological symptoms in diabetes mellitus patients. The implementation of ACT consists of 6 – 10 sessions and several articles recommend including diabetes education in the initial session of giving ACT. ACT is effective for treating psychological problems such as depression, anxiety, and distress in patients with diabetes mellitus.